Student’s Experiences on Their Thesis Proposal Seminar - Sugeng Pradikto (CV. AFDIFAL MAJU BERKAH, 2023)
This study aims to investigate students’ experiences based on their thesis proposal seminar for Economic Education Students’ Department Study Program at Universitas PGRI Wiranegara. The researcher used the questionnaire to get the data from the students’ experiences based on their thesis proposal seminar at three stages, starting from the beginning up to the end. Based on the result shown that for the first table explained before the thesis proposal seminar presentation exposed that most students’ good understanding of the learning objective of the seminar course (83,3%) and that they felt confident and supported by many resources. For the second table explained during the seminar session, most students agree (70,9%) that seminar encouraged their ideas to share and learn from others, but (45,8%) disagree that group discussion in a presentation session seminar is better than lecturing. The last table explained after the seminar session, showed the students that (93,8%) believe that post-seminar questions and feedback are informative both from lectures and from their friends, also (70,8%) agree that the seminar success through good preparation, and (81,3%) that classmates’ participation supported the seminar’s success.